A Framework for Achieving an Adequate and Effective Health Care System Through Primary Care in Grenada: A Systematic Review - McLeish MD MSc PgDip (Family Medicine), Tiffany (Journal of Family Medicine, 2026)
With an emphasis on the implications for Grenada, this systematic study delves into the complexities of setting up a successful primary healthcare system in tiny island states. It is emphasized how crucial primary healthcare is as a community-based, preventative paradigm and how it improves general health outcomes. Many stories of success from similar small island nations show the value of proactive health education and community engagement. One important consideration is financial sustainability, which is demonstrated by the success of many funding schemes in maintaining basic healthcare. Key components identified include public-private partnerships, international collaborations, and novel funding structures. These provide Grenada with useful knowledge for the purpose of mobilizing resources strategically. It has been determined that effective organization frameworks and proactive stakeholder involvement are essential to primary healthcare success. In response to the particular requirements of tiny island populations, collaborative initiatives promote inclusive and responsive healthcare systems. Education initiatives and competitive pay are two tactics used to prevent brain drain that help keep qualified workers in the workforce and ensure the sustainability of the healthcare system. The requirements for infrastructure include the thoughtful positioning of medical facilities, the incorporation of technology, and creative approaches to transportation problems. Especially in rural locations, these factors are critical to improving accessibility and the general effectiveness of healthcare delivery. The review’s conclusions point to the need for a customised strategy for Grenada. Key elements include proactive health education, diverse funding options, cooperative governance, healthcare professional retention plans, and strategic infrastructure development. Grenada can set the stage for a robust and efficient primary healthcare system that takes into account the particular advantages and disadvantages of its tiny island setting by implementing these findings into policy and practise.
Keywords: Primary healthcare; Health system strengthening; Small island developing states; Health policy and governance; Grenada